Correlation of TP53 and MDM2 genotypes with response to therapy in sarcoma. Issue 5 (16th November 2012) - Ohnstad, Hege O.; Castro, Russell; Sun, Jinchang; Heintz, Karen‐Marie; Vassilev, Lyubomir T.; Bjerkehagen, Bodil; Kresse, Stine H.; Meza‐Zepeda, Leonardo A.; Myklebost, Ola
Abstract BACKGROUND: Relatively few sarcomas harbor TP53 (tumor protein p53) mutations, but in many cases, amplification of MDM2 (murine double minute 2) effectively inactivate p53. The p53 pathway activity can also be affected by normal genetic variation. METHODS: The mutation status of TP53 and expression of MDM2, TP53, and their genetic variants SNP309 and R72P (Arg72Pro) were investigated in 125 sarcoma patient samples and 18 sarcoma cell lines. Association of the different genotypes and gene aberrations with chemotherapy response and survival, as well as response to MDM2 antagonists in vitro was evaluated. RESULTS: Twenty‐two percent of the tumors had mutant TP53 and 20% MDM2 gene amplification. Patients with wild‐type TP53 (TP53Wt) tumors had improved survival (P < .001) and TP53Wt was an independent prognostic factor (hazard ratio = 0.41; 95% confidence interval = 0.23‐0.74; P = .03). Interestingly, there was a trend toward longer time to progression after chemotherapy for tumors with the apoptosis‐prone p53 variant R72 (P = .07), which was strongest with doxorubicin/ifosfamide‐based regimens (P = .01). Liposarcomas had low R72 frequency (33% versus 56%), but increased levels of MDM2 and MDM4 (51% and 11%, P < .001). MDM2 overexpression on a TP53Wt background predicted better response to MDM2 antagonist Nutlin‐3a, irrespective of R72P or SNP309 status. CONCLUSIONS: Improved survival after chemotherapy was found in patients with TP53Wt tumors harboring the R72 variant. MDM2 overexpression in TP53Wt tumors predicted good response to MDM2 antagonists, irrespective of R72P or SNP309 status. Thus, detailed TP53 and MDM2 genotype analyses prior to systemic therapy are recommended. Cancer 2013. © 2012 American Cancer Society.